Molecular Insights into the Local Anesthetic Receptor within Voltage-Gated Sodium Channels Using Hydroxylated Analogs of Mexiletine - Desaphy, Jean-François; Dipalma, Antonella; Costanza, Teresa; Carbonara, Roberta; Dinardo, Maria Maddalena; Catalano, Alessia; Carocci, Alessia; Lentini, Giovanni; Franchini, Carlo; Conte Camerino, Diana (Frontiers in Pharmacology, 2012)
We previously showed that the β-adrenoceptor modulators, clenbuterol and propranolol, directly blocked voltage-gated sodium channels, whereas salbutamol and nadolol did not (Desaphy et al., 2003), suggesting the presence of two hydroxyl groups on the aromatic moiety of the drugs as a molecular requisite for impeding sodium channel block. To verify such an hypothesis, we synthesized five new mexiletine analogues by adding one or two hydroxyl groups to the aryl moiety of the sodium channel blocker and tested these compounds on hNav1.4 channels expressed in HEK293 cells. Concentration-response relationships were constructed using an holding potential of -120 mV at 0.1 Hz (tonic block) and 10 Hz (use-dependent block) stimulation frequencies. The half-maximum inhibitory concentrations (IC50) were linearly correlated to drug lipophilicity: the less lipophilic the drug, minor was the block. The same compounds were also tested on F1586C and Y1593C hNav1.4 channel mutants, to gain further information on the molecular interactions of mexiletine with its receptor within the sodium channel pore. Alteration of tonic block suggests that the aryl moiety of mexiletine may interact either directly or indirectly with Phe1586 in the closed sodium channel to produce low-affinity binding block, and that this interaction depends on the electrostatic potential of the drug aromatic tail. Alteration of use-dependent block suggests that addition of hydroxyl groups to the aryl moiety may modify high-affinity binding of the drug ammine terminal to Phe1586 through cooperativity between the two pharmacophores, this effect being mainly related to drug lipophilicity. Mutation of Tyr1593 further impaired such cooperativity. In conclusion, these results confirm our former hypothesis showing that the presence of hydroxyl groups to the aryl moiety of mexiletine greatly reduced sodium channel block, and provide molecular insights into the intimate interaction of local anesthetics with their receptor.